Fatty Acids in the Genus Bacillus I. Iso- and Anteiso-Fatty Acids as Characteristic Constituents of Lipids in 10 Species - Kaneda, Toshi (1967)
Fatty acids produced by 22 strains of 10 species of the genus Bacillus were analyzed on a very efficient and selective gas-liquid chromatographic column. All of the 10 species, alvei, brevis, cereus, circulans, licheniformis, macerans, megaterium, polymyxa, pumilus, and subtilis, produced eight fatty acids, six branched (anteiso-C(15), anteiso-C(17), iso-C(14), iso-C(15), iso-C(16), and iso-C(17)) and two normal (n-C(14) and n-C(16)). In all cases, the six branched-chain fatty acids made up over 60% of the total fatty acids. In addition to the eight fatty acids, B. cereus produced four extra fatty acids, three branched (anteiso-C(13), iso-C(12), and iso-C(13)) and one monoenoic-n-C(16). Furthermore, there were distinct differences in the relative amounts of fatty acids produced between B. cereus and the remaining nine species. B. cereus produced iso-C(15) fatty acid in the largest amount on a glucose-yeast extract medium as well as on Pennassay Broth. On the other hand, for the remaining nine species, anteiso-C(15) fatty acid was the major fatty acid from the glucose-yeast extract medium, whereas the amount of iso-C(15) fatty acid from Penassay Broth became comparable to that of anteiso-C(15) fatty acid. Mechanisms and various factors affecting the fatty acid distribution pattern in the 10 Bacillus species are discussed.